From Order to Satisfaction: Examining Food, Service, and Value Drivers of Customer Satisfaction in the Fast-Food Industry - Lay Hong Tan; Tek Yew Lew; Yee Ros Tan; Wan Ling Tan; Wei Chi Tan; Wei Len Tan; Yee Ling Tan; Anees Jane Ali; Daisy Mui Hung Kee (AIBPM Publisher, 2025)
Customer satisfaction is a critical determinant of competitiveness in the fast-food industry, even for global leaders like McDonald’s, which is widely recognized for efficiency, consistency, and strong branding. Despite its success, adapting to evolving customer expectations remains essential. This study aims to evaluate the factors influencing customer satisfaction at McDonald’s in Malaysia, focusing on food quality, service quality, pricing and value, product variety, and service method. A quantitative survey was conducted with 100 respondents using structured questionnaires. The findings indicate that customer satisfaction is most strongly influenced by service method (? = 0.449) and product variety (? = 0.279), while food quality, service quality, and pricing and value showed weaker effects and did not significantly predict satisfaction. The overall model explained 49% of the variance in customer satisfaction (R² = 0.492). These results highlight that customers place the greatest emphasis on convenience, efficiency, and diverse menu options. McDonald’s should therefore prioritize enhancing service delivery across dine-in, drive-thru, and self-service kiosks, while maintaining food quality and competitive pricing as baseline expectations. Overall, this study provides practical insights for improving customer satisfaction and offers strategic implications for fast-food chains in highly competitive markets